PENEMPELAN LARVA SIPUT LAUT (HALIOTIS VARIA) : SUATU PERCOBAAN DI LABORATORIUM - Ompi, Medy; Kawung, Nickson; Calvyn, Calvyn; Sondak, F. A. (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2010)
Settlement of abalone (Haliotis varia) focusing on substrate quality and larval behavior were studied. Four types of substrate, shell and mucous, algae Gracilaria sp and Halimeda sp, and plastic petri-dish were used to test whether the larva might respond and settle on those substrates. At the same time, the mortality of larvae was also determined during the settlement. Without petri-dish, substrate of shell and mucous, algae, as well as polyvinyl chloride (PVC) plate were tested to find out substrate preferences when settlements occured. The result showed that variation of substrata, shell and mucous, algae and plastic ?petri-dish? possessed a stimuli responded by larva to settle. Shell and mucous as well as substrate algae were attractive among of substrata, since high of settlement on it were recorded. High larval mortality on shell and mucous as well as on substrata of algae were recorded. Substrate of shell and mucous and alga were favorable to substrata when settling. Several factors affecting settlement of larval abalone were discussed.